Korelasi antara Peran Orang Tua terhadapKedisiplinkan Anak Melaksanakan Sholat - Kamilatunnisa Kamilatunnisa; Lailatul Fitria; Resty Norlelawati; Muhammad Zaini; Durrtun Nimah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine whether there is a correlation between the role of parents and children's discipline in performing prayer in the RT 02 neighborhood of Manurung Village, Tanah Bumbu Regency, based on the assumption that parental involvement is linked to children's prayer discipline. A quantitative approach was employed. The results indicate that the role of parents in guiding children to perform prayer is categorized as